Mathematical modelling through semiotic reasoning: Exploring elementary school students' problem-solving processes - Sony Darmawan; Adinda Silvy Wijaya; Dyah Worowirastri Ekowati; Moh. Mahfud Effendi; Akhsanul In'am; Laraib Aftab Khokhar; Salatou Touray; Rabia Rasheed (Research and Development in Education (RaDEn), 2026)
Background-Mathematical reasoning has become important in mathematics education, particularly in understanding how students interpret and solve word problems. Semiotic reasoning, involving signs, symbols, verbal expressions, and visual representations, is essential for explaining students’ construction of mathematical meaning. Objectives-This study explores semiotic reasoning models used by elementary school students in solving word problems related to distance, speed, and time. Methods-This study employed a descriptive qualitative approach through observation, interviews, and documentation of students’ written answers. The data identified students’ semiotic reasoning models in solving word problems. The subjects were Grade 5 and 6 students of SD Muhammadiyah 9 Malang. Results-Students’ semiotic reasoning models were identified through problem-solving analysis and interview confirmation. The findings revealed three models: A-A-I-G-I-J-A-J, A-I-G-I-J, and A-A-A-I-G-A-A-A-A-J, where A (Analysis), I (Integration), G (Generalisation), and J (Justification). The first model shows reflective integration of symbolic, verbal, and graphic representations. The second indicates direct connection between symbols and justification. The third reflects repeated analytical evaluation to ensure the accuracy of students’ mathematical problem-solving processes and meaningful representation use. Conclusions-These findings reveal the importance of semiotic reasoning in facilitating students’ understanding of abstract mathematical concepts and contributing to adaptive, multimodal mathematics learning strategies.